Regional development disparity and mapping of economic potential in East Nusa Tenggara province - Frederic Winston Nalle; Yuliati Sengkoen; Rikhardus Bria Seran; Winda Aulia Rahmarini (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
East Nusa Tenggara Province is one of the provinces in Indonesia in the form of an archipelago and geographically borders directly with the State of Timor Leste. This province has a problem with a fairly high poverty rate, in fact it was recorded as the 3rd highest in Indonesia after the provinces of Papua and West Papua. Because it is an archipelagic province, the problems of disparity in regional development, income inequality and poverty cannot be avoided. The existence of this disparity symptom does not only lie in regional development, but this disparity occurs in the income and GDP-forming sectors. Therefore the main goal to be achieved in this research is to identify areas in NTT Province which are still classified as lagging behind, and how to find the economic base sector as a leading sector so that it can be used as a locomotive for regional development so that in turn it is able to reduce regional inequality, income distribution and poverty. The analytical tools used are Theil Entrophy Analysis, Klasen Typology, Location Quintient (LQ) Analysis and Dynamic Location Quintien (DLQ) Analysis. The data needed is secondary data in the form of published documents from the BPS Province of NTT from 2012-2018 for the purposes of analysis such as GRDP data, population and per capita income for each district in the province of NTT. The results of the analysis found that there were 3 regencies that were classified as developed and fast growing, 3 regencies which were categorized as developed but depressed areas.